2009
DOI: 10.4081/rr.2009.e12
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcitonin in management of musculoskeletal pain

Abstract: Calcitonin was discovered more than 40 years ago and the scientific community continues to debate the primary and secondary pharmacological actions of calcitonin. Presently calcitonin is accepted by agencies only for treatment of osteoporosis, but many studies have indicated an effect on pain in many different experimental settings both pre-clinically and clinically. The effects of calcitonin on clinical pain conditions have received increasing attention in the past decades, although a consensus on mode of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Modulatory effects on CPM have been found by dexmedetomidine (a selective α(2)‐adrenoceptor agonist) (Baba et al., ) and apomorphine (a non‐specific dopamine agonist) (Treister et al., ). Recently it has been suggested that calcitonin may interact with the descending pain modulation as calcitonin interacts with serotonin, and a synergetic analgesic effect between calcitonin and serotonin reuptake inhibitor antidepressants has been shown (Arendt‐Nielsen et al., ) indicating various alternative options to interact with the descending pathways.…”
Section: How To Interact With the Central Sensitisation In Chronic Pain?mentioning
confidence: 99%
“…Modulatory effects on CPM have been found by dexmedetomidine (a selective α(2)‐adrenoceptor agonist) (Baba et al., ) and apomorphine (a non‐specific dopamine agonist) (Treister et al., ). Recently it has been suggested that calcitonin may interact with the descending pain modulation as calcitonin interacts with serotonin, and a synergetic analgesic effect between calcitonin and serotonin reuptake inhibitor antidepressants has been shown (Arendt‐Nielsen et al., ) indicating various alternative options to interact with the descending pathways.…”
Section: How To Interact With the Central Sensitisation In Chronic Pain?mentioning
confidence: 99%
“…At present there is a considerable debate in the literature on the effect of sCT on pain, albeit no long term RCT have investigated these effects carefully 37 . In the CSMC021C2301 study we observed an effect on pain, stiffness and function, but as a hierarchical testing procedure was applied for the co-primary endpoints no beneficial treatment effect can be claimed as the first endpoint of JSN failed to show significance.…”
Section: Pain and Functionmentioning
confidence: 99%